Progress in epigenetic histone modification analysis by mass spectrometry for clinical investigations. (3rd September 2015) - Önder, Özlem; Sidoli, Simone; Carroll, Martin; Garcia, Benjamin A
Abstract : Chromatin biology and epigenetics are scientific fields that are rapid expanding due to their fundamental role in understanding cell development, heritable characters and progression of diseases. Histone post-translational modifications (PTMs) are major regulators of the epigenetic machinery due to their ability to modulate gene expression, DNA repair and chromosome condensation. Large-scale strategies based on mass spectrometry have been impressively improved in the last decade, so that global changes of histone PTM abundances are quantifiable with nearly routine proteomics analyses and it is now possible to determine combinatorial patterns of modifications. Presented here is an overview of the most utilized and newly developed proteomics strategies for histone PTM characterization and a number of case studies where epigenetic mechanisms have been comprehensively characterized. Moreover, a number of current epigenetic therapies are illustrated, with an emphasis on cancer.